Design, development and optimization of gastro-retentive floating in-situ gels loaded with carvedilol microspheres using response surface methodology - Kukati Latha; Rahman Aisha; Fatima Aymen; Menon Vyshak R; Lakshmi SVVNSM (Acta Marisiensis - Seria Medica)
Aim: The goal of this study was to formulate and optimize gastro-retentive floating in-situ gel comprising optimized microspheres by Box-Behnken design.